Language Barriers in Communication Faced By Indonesian Students in Australia - Cherisa Angelika; Putri Rindu Kinasih; Veronika Ita Karina Tarigan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Language plays a crucial role in communication as it occurs in every individual's or group's interaction. When visiting a country that speaks a foreign language, it is essential to effectively communicate in that language. This research studied international students who qualified to study abroad yet still experienced some language barriers while living in Australia. This study aims to find what are the types, effects, and their strategy to prevent the language barrier they experienced. A qualitative approach was applied in this research and semi-structured interviews were conducted with 3 Indonesian students who study in Australia. The result shows that the types of language barriers faced by the participants were: technical jargon, badly expressed message, and unclarified assumptions. Then, confusion was the primary impact of the language barrier on each interviewee. Lastly, the strategies they used to prevent the language barrier were: speaking slowly and clearly, asking for clarification, frequently checking for understanding, and being patient. In addition, it is suggested that international students find out more about the culture through local television movies or series so that they become familiar with the local terms.